Convergencia Digital: Nuevos perfiles profesionales del periodista (2015)
Journalism is changing with the development of Informationand Communication Technology (TIC abbreviation in Spanish)and the emergence of new online media that are changing thetraditional work routines, content, production, distribution,and consumption of information. This new stage is markedby the digital convergence in its various dimensions and themultiplication of new platforms, tools, and formats reception,dissemination and interaction that invite to change journalists’professional profiles and to give a second thought to their newskills to practice. To build the new profile of the journalist, aqualitative and quantitative research through surveys, depthinterviews and discussion groups applied to the various actorsof media companies and managers of journalism programsin Colombia were conducted from three professional skills:business-technological, content communicative and usersprofessional. It was concluded with the construction of a map ofcompetencies of a journalist in a digital context, among others,to produce contents, languages and multimedia narratives. toimplement technologies and networks, to create informativeand interactive formats consistent with the preferences of theaudience, and to adapt to the new communication ecosystem.